Knowledge, attitudes and practices with regard to schistosomiasis prevention and control: Two cross-sectional household surveys before and after a Community Dialogue intervention in Nampula province, Mozambique. - Christian Rassi; Sandrine Martin; Kirstie Graham; Monica Anna de Cola; Celine Christiansen-Jucht; Lauren E Smith; Ercílio Jive; Anna E Phillips; James N Newell; Marilia Massangaie (Public Library of Science (PLoS), 2019)
BACKGROUND:The Community Dialogue Approach is a promising social and behaviour change intervention, which has shown potential for improving health seeking behaviour. To test if this approach can strengthen prevention and control of schistosomiasis at community level, Malaria Consortium implemented a Community Dialogue intervention in four districts of Nampula province, Mozambique, between August 2014 and September 2015. METHODOLOGY/PRINCIPAL FINDINGS:Cross-sectional household surveys were conducted before (N = 791) and after (N = 792) implementation of the intervention to assess its impact on knowledge, attitudes and practices at population level. At both baseline and endline, awareness of schistosomiasis was high at over 90%. After the intervention, respondents were almost twice as likely to correctly name a risk behaviour associated with schistosomiasis (baseline: 18.02%; endline: 30.11%; adjusted odds ratio: 1.91; 95% confidence interval: 1.14-2.58). Increases were also seen in the proportion of people who knew that schistosomiasis can be spread by infected persons and who could name at least one correct transmission route (baseline: 25.74%; endline: 32.20%; adjusted odds ratio: 1.36; 95% confidence interval: 1.01-1.84), those who knew that there is a drug that treats the disease (baseline: 29.20%, endline: 47.55%; adjusted odds ratio: 2.19; 95% confidence interval: 1.67-2.87) and those who stated that they actively protect themselves from the disease and cited an effective behaviour (baseline: 40.09%, endline: 59.30%; adjusted odds ratio: 2.14; 95% confidence interval: 1.40-3.28). The intervention did not appear to lead to a reduction in misconceptions. In particular, the belief that the disease is sexually transmitted continued to be widespread. CONCLUSIONS/SIGNIFICANCE:Given its overall positive impact on knowledge and behaviour at population level, Community Dialogue can play an important role in schistosomiasis prevention and control. The intervention could be further strengthened by better enabling communities to take suitable action and linking more closely with community governance structures and health system programmes.